CAFF CBMP Report No. 4 - Shorebirds Expert Network Monitoring Plan. Monitoring Arctic-nesting Shorebirds: An International Vision for the Future. - Arctic Council , Conservation of Arctic Flora and Fauna Working Group (CAFF International Secretariat, 2004)
Shorebirds Expert Network Monitoring Plan. Monitoring Arctic-nesting Shorebirds: An International Vision for the Future. Conclusions from The Pan-Arctic Shorebird/Wader Monitoring and Research Workshop, Denmark, 3-6 December 2003.